Arthroscopic Shoulder Stabilization in the High-Risk Young Athlete: Return to Sport and Second Surgery Rates. Issue 7 (30th July 2018) - Cordasco, Frank A.; Lin, Brian; Ling, Daphne; Calcei, Jacob G.
Objectives: Shoulder instability in the young athlete has become an increasingly significant clinical problem in recent years. This high-risk population of athletes less than 25 years of age is a difficult cohort to manage because they have high failure rates with non-operative treatment and they reportedly have the lowest return to sport (RTS) rates and highest second surgery rates following arthroscopic shoulder stabilization compared to older patients. The purpose of this retrospective study is to evaluate the two-year clinical outcomes of a cohort of high-risk athletes less than or equal to 22 years of age following arthroscopic shoulder stabilization with a focus on RTS and incidence of second surgery. Methods: The primary outcomes evaluated were RTS and revision surgery following arthroscopic shoulder stabilization performed by the senior author at minimum follow-up of 24 months. Athletes were excluded if they had > 5 pre-operative episodes of instability, significant bone loss or had primary posterior instability. Demographic data was recorded including age, sex, BMI, last recorded range of motion, # episodes of recurrent instability, and revision surgery. A brief survey was completed regarding their shoulder instability history, sports prior to surgery, sports returned to following surgery, satisfaction with and level of RTS, time at which return to sports was achieved, recurrent instability, revision operations, and single assessment numeric evaluation (SANE) score. Results: A total of 67 athletes met inclusion criteria, with a mean age of 17.4 years (range, 13-22 years). There were 19 females (28%) and 48 males (72%). The mean number of instability events was 2 (range 0-5), 57% in the dominant arm and 43% in the non-dominant arm. Evaluation of RTS, demonstrated that 59 (88%) were able to RTS with 56 (84%) of those returning to the same level or higher, while 8 (12%) patients did not RTS for reasons other than recurrent instability or apprehension. Among the 59 patients who RTS, the average time to return was 7.3 months (range: 5-12 months) and baseball and football were the most common sports. There was a gender specific difference with respect to RTS and revision surgery. The male RTS rate was 94% compared to the female rate of 74%. Four of 67 (6%) patients underwent revision stabilization 11 to 36 months for recurrent instability, however all were male athletes 4/48 (8%). There were no female athletes who required revision surgery. Patient reported mean SANE score was 88 (SD, ±15). Conclusion: Shoulder instability in the young high-risk athlete is a complex problem with a relatively high rate of recurrence and revision surgery in the literature. In our case series, we found a relatively low reoperation rate (6%) with a high rate of RTS (88%), at an average time of 7.3 months. There was a gender specific difference with respect to RTS and revision surgery. The male RTS rate was 94% and revision surgery rate was 8% (4/48) while the female RTS rate was 74% and revision surgery rate was 0%. The athletes reported a return to near full function with an average SANE score of 88. We believe the improved outcomes in this cohort of high risk young athletes are related to the pre-operative selection criteria excluding those athletes with a greater number of pre-operative episodes of instability and those with significant bone loss and bipolar lesions as open stabilization and bone augmentation (Latarjet) are more predictable operations in athletes with these risk factors.